2005
DOI: 10.1007/s10803-005-3289-y
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Visual Orienting to Gaze- and Arrow-Cues in Adults with High Functioning Autism

Abstract: The present study investigates visual orienting to directional cues (arrow or eyes) in adults with high functioning autism (n = 19) and age matched controls (n = 19). A choice reaction time paradigm is used in which eye- or arrow direction correctly (congruent) or incorrectly (incongruent) cues target location. In typically developing participants, the visual orienting reflex is longer for eyes than for arrows. Right side cueing, but not left side cueing, induced a congruence effect for eyes, while this effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
96
3
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 51 publications
10
96
3
9
Order By: Relevance
“…When control fathers and mothers in the current study were compared with the controls in the study of Vlamings et al (2005) it became clear that they demonstrated a different pattern of reaction times. Control fathers had a symmetrical congruency effect on the eye task and mothers did not show a significant effect of congruency on either side of the eye task.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…When control fathers and mothers in the current study were compared with the controls in the study of Vlamings et al (2005) it became clear that they demonstrated a different pattern of reaction times. Control fathers had a symmetrical congruency effect on the eye task and mothers did not show a significant effect of congruency on either side of the eye task.…”
Section: Discussionmentioning
confidence: 81%
“…It is interesting to note that the pattern of reaction times on the eye task shown by fathers as well as mothers with an autistic child is exactly the opposite of what was shown by the young control adults in the study of Vlamings et al (2005), namely, these controls only showed a significant congruency effect when eyes looked to the right. When control fathers and mothers in the current study were compared with the controls in the study of Vlamings et al (2005) it became clear that they demonstrated a different pattern of reaction times.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Esta pesquisa não considerou se o "olhar para objeto(s)" (OJ) foi decorrente ou não de situações de atenção compartilhada, nas quais, os bebês dirigem seu olhar ao foco de atenção de outra pessoa (8,10,13,23,28) . Isto constituiria uma dificuldade para bebês até os seis meses (24) , porém, na amostra, pareceu ocorrer algumas vezes, especialmente na quinta filmagem.…”
Section: Discussionunclassified